Chapter 3: Treatment Algorithms for Gastrointestinal Disorders (Handbook of Treatment Algorithms for Medical and Pharmacy Students, 2025)
AuthorMr. Gourab Saha,Associate Professor, Department of Pharmaceutics, College of Pharmaceutical Sciences, Berhampur, Mohada, Odisha, IndiaAbstractGastrointestinal treatment algorithms focus on resolving symptoms, healing mucosal damage, and managing underlying etiology. The algorithm for gastroesophageal reflux disease (GERD) is a stepwise approach, commencing with lifestyle modifications and proceeding to an 8-week trial of proton pump inhibitors (PPIs). Failure of this trial, or the presence of alarm features, triggers endoscopic evaluation. Peptic ulcer disease (PUD) management is bifurcated by cause: H. pylori-positive ulcers are treated with an eradication algorithm (e.g., bismuth quadruple therapy), while NSAID-induced ulcers require PPI therapy and cessation of the offending agent. The algorithm for inflammatory bowel disease (IBD) is stratified by disease type (Crohn's vs. Ulcerative Colitis) and severity, utilizing a "step-up" or "top-down" approach with 5-ASAs, corticosteroids, immunomodulators, and biologics to induce and maintain remission. Celiac disease management is a singular algorithm centered on a strict, lifelong gluten-free diet and nutritional monitoring. Hepatitis algorithms are virus-specific: Hepatitis A is managed supportively; chronic Hepatitis B treatment is guided by viral load and liver inflammation, using nucleos(t)ide analogs for long-term suppression; and Hepatitis C is managed with a curative, pangenotypic direct-acting antiviral (DAA) regimen.Keywords: Gastrointestinal Algorithms, GERD, Peptic Ulcer Disease, Inflammatory Bowel Disease, Celiac Disease, HepatitisVIEW PDF